Heresy and Authority in the Thought of Théodore de Bèze - Panetta, Odile (Renaissance and Reformation / Renaissance et Réforme, 2022)
This article offers a comprehensive account of Théodore de Bèze’s views on the punishment of heretics and a reflection on their broader significance. The core of its analysis focuses on Bèze’s earliest political work, the Anti-Bellius. It provides an assessment of five aspects of Bèze’s discussion: the legal basis for the punishment of heresy; the respective roles of civil and ecclesiastical authorities in disciplining heretics; the definition of heresy; the consensus of all relevant authorities on the matter; and the possibility of grounding justifications for coercion on absolute claims to religious truth. The concluding section examines the enduring role played by these ideas both in Bèze’s own later writings and in subsequent Reformed discussions of the subject. The historical import of Bèze’s formulations is shown to lie in their lasting influence and in the deeper reflections on the nature of political authority on which these formulations rested.